Insecticidal and growth inhibitory potential of Streptomyces hydrogenans DH16 on major pest of India, Spodoptera litura (Fab.) (Lepidoptera: Noctuidae) - Kaur, Talwinder (BioMed Central, 2014)
BACKGROUND: Destructive impacts of insecticides on non targeted populations necessitate the development of an eco friendly pest control method. Streptomyces spp. are rich source of bioactive secondary metabolites which may provide valuable alternatives to chemical insect-control agents as they can be less toxic and readily biodegradable. Because of its potent biocontrol attributes, ethyl acetate extract of Streptomyces hydrogenans DH16, a soil isolate, was tested to assess its anti-insect potential against polyphagous noctuid, Spodoptera litura. RESULTS: The secondary metabolites in the ethyl acetate extract of S. hydrogenans DH16 exhibited larvicidal and growth inhibitory activities. The results indicated that highest concentration of 1600 μg/ml was significantly effective as 70% larval, 66.66% prepupal and 100% pupal mortality was noticed. The metabolites also prolonged the larval developmental period. The LC50 and LC90 values were 1337.384 and 2070.516 μg/ml, respectively for the insect. Negative effects of S. hydrogenans were also observed on development of the insect. Significant decline in adult emergence, adult longevity, fecundity and % hatching was recorded at higher concentrations along with morphological abnormalities as compared to control. Significant decrease in relative growth and consumption rate, efficiency of ingested and digested food and increase in approximate digestibility in larvae reared on diet supplemented with ethyl acetate extract accounts for the toxic as well as anti-nutritive nature of extract. CONCLUSION: Secondary metabolites in the fermentation broth from S. hydrogenans were toxic to the larvae at higher concentrations whereas lower concentrations significantly reduced the reproductive potential of S. litura. Therefore, these metabolites show considerable potential for incorporation in pest management programmes as new biopesticidal formulation.